HUBUNGAN ANTARA WORK LIFE BALANCE DAN WORK ENGAGEMENT PADA KARYAWAN DI PT.X - Erika Lie; Sukmarani (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2023)
Â Although work-life balance is not a new topic, the multidimensional perspective of work life balance has not been extensively studied. The purpose of this research is to evaluate the relationship between the dimensions of work-life balance and work engagement among employees, using a multidimensional perspective of work-life balance. This study used a qualitative approach, distributing online questionnaires to 37 participants, utilizing the Work Life Balance Scale andthe Utrecht Work Engagement Scale version 9 as measurement tools. Data analysis was conducted using Pearsonâ€™s Correlation statistical technique. The findings of the study showed a significant positive correlation between the demands dimension of work-life balance and work engagement. Similarly, a significant positive correlation was indicated between the resources dimension of work-life balance and work engagement. These findings suggest that studying work-life balance from a multidimensional perspective helps to achieve a more specific understanding of work-life balance, particularly in relation to work engagement. The multidimensional model of work-life balance is encouraged to be more widely used in the future research studies.